The Photovoice Project: Fostering Students' Autonomous, Collaborative, and Authentic Business/Engineering English Learning Experiences - NUR, Syauqiyah Awaliyah Alfiani; PRIYA, S. Sabitha Shunmuga; ARDININGTYAS, Sri Yulianti (Politeknik Negeri Ujung Pandang, 2024)
This perspective article elaborates an instructional approach to business English learning utilizing a photovoice project as a strategy to promote a real-world learning encounter. In professional and vocational colleges, project-based learning (PBL) is an instructional strategy for promoting autonomous, collaborative, and authentic learning nuances. This article sheds light on how photovoice project fosters the students’ technical and business English learning experiences. The project empowers students to take charge of their learning, work collaboratively, and engage in real-world business context. This paper presents the concept of photovoice, learners’ autonomy and collaboration towards photovoice, authentic business English learning encounters, technology-integrated photovoice, project evaluation, and case studies on photovoice project. On top of that, language teachers can utilize project-based photovoice as a valuable tool for promoting innovative and engaging business English learning activities, thus providing students with contextual-based learning environment and preparing them for the real business world. It also brings several implications: 1) for vocational English teachers, implementing photovoice projects offers a powerful tool to create innovative and engaging learning activities, 2) for students, these projects provide a contextualized learning environment that prepares them for the real business world by developing practical language skills and industry-specific knowledge, and institutions will benefit by fostering an educational approach that bridges classroom learning with real-world applications, thereby enhancing the overall quality and relevance of their programs.